Investigation of design space in manufacturing meta-biomaterials by additive manufacturing - Siti Rohaida, Mohamed; Saiful Anwar, Che Ghani (IOP Publishing, 2021)
Topology features such as interconnectivity, pore shape and size, porosity, struts thickness, and used materials play the key roles for mechanical and biological properties of meta-biomaterials structures. However, the influences of morphological geometries on the mechanical and biological properties are not certainly intuitive. This paper develops parametric model that use to visualize the morphological geometries of unit cell of meta-biomaterials on design space that governing the manufacturing limitation, mechanical and biological requirements. The selected samples within design spaces tested to determine manufacturing accuracy and effective elastic modulus by finite element analysis. The geometries discrepancies between designed models and manufactured samples obtained percentage of average errors of 13% for diamonds structures and 21% for square structures. The proposed technique yielded average error reduced to 74.4% for diamond structures and 44.4% for square structures of effective elastic modulus from theoretical calculation. The approach and the implications of the results discussed in the context of mechanical and biological criteria with highlight of advantages and limitations of meta-biomaterials manufactured by additive manufacturing for orthopaedic implants